Morphofunctional characteristics of highly sports qualified badminton players - Zakharyeva N.N. ,; Barchukova G.V. ,; Karpov G.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the morphofunctional characteristics of successful highly qualified badminton players with a high competitive rating, performing in men's singles. Methods and structure of the study. The survey involved 14 athletes - badminton players - highly qualified men with a high rating in the Russian Federation, regularly participating in prestigious competitions with high sporting results. For a comparative analysis, anthropometric indicators of 248 healthy untrained men, aged 19-23 years, living in Moscow, were used. Results and conclusions. It has been established that the weight and height parameters of badminton players with a high rating in badminton in the Russian Federation do not differ from those of badminton players with high ratings in the BWF. When studying the girth dimensions of the body of badminton players, an asymmetry was noted in the girth sizes of the extremities of the playing arms and legs, more pronounced in the girth sizes of large muscle masses of the shoulder and thigh. When performing the Romberg test with the leg fixed on the knee, athletes showed high results in vertical stability. The results of badminton players performing the Ruffier test indicate the dominance of a satisfactory test result, which indicates the need to develop aerobic endurance when practicing badminton.